2014
DOI: 10.1111/ajps.12108
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing and Compliance in the Judicial Hierarchy

Abstract: One way that principals can overcome the problem of informational asymmetries in hierarchical organizations is to enable whistleblowing. We evaluate how whistleblowing influences compliance in the judicial hierarchy. We present a formal model in which a potential whistleblower may, at some cost, signal noncompliance by a lower court to a higher court. A key insight of the model is that whistleblowing is most informative when it is rare. While the presence of a whistleblower can increase compliance by lower cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…Existing theories have demonstrated that a lower court's private information about a case's facts creates an incentive for an upper court to defer (e.g., Beim 2017; Beim, Hirsch, and Kastellec 2014;Cameron, Segal, and Songer 2000;Carrubba and Clark 2012;Clark and Carrubba 2012;Lax 2012). However, the particular way that fact finding is conceptualized (and therefore modeled) matters for understanding both the scope and form of this deference (see Stephenson 2011).…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%
See 1 more Smart Citation
“…Existing theories have demonstrated that a lower court's private information about a case's facts creates an incentive for an upper court to defer (e.g., Beim 2017; Beim, Hirsch, and Kastellec 2014;Cameron, Segal, and Songer 2000;Carrubba and Clark 2012;Clark and Carrubba 2012;Lax 2012). However, the particular way that fact finding is conceptualized (and therefore modeled) matters for understanding both the scope and form of this deference (see Stephenson 2011).…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%
“…Second, this article adds to recent models focused on the role of opinion writing in managing hierarchical relationships between courts, and between courts and legislatures (e.g., Beim, Hirsch, and Kastellec 2014;Clark and Carrubba 2012;Staton and Vanberg 2008). Clark and Carrubba (2012) conceive of opinions as consisting of legal rules and persuasive quality.…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%
“…Although dissenting opinions at the Supreme Court have become more common (Corley et al ), unanimity is a powerful norm at the U.S. Courts of Appeals (Cross ; Kim ). Dissenters are argued to be whistleblowers in the federal judicial hierarchy, signaling potential deviation from Supreme Court or circuit precedent or procedure (Beim et al ; Blackstone & Collins ; Cross & Tiller ; Hazelton et al ). The presence of a dissent has long been thought to be a factor in decisions on certiorari (Tanenhaus et al ; Ulmer et al ).…”
Section: Separate Opinion Writing In the Federal Courtsmentioning
confidence: 99%
“…2 In the context of lower and upper court relationships, Carubba and Zorn (2010), Carubba and Clark (2012), Clark and Carubba (2012), Beim, Hirsch, and Kastellec (2014), and Hübert (2019) consider how a lower court may strategically issue a judgement to avoid being overturned by an upper court. These papers generally consider a one-shot game and cannot explain the evolution of jurisprudence over time.…”
Section: Literature Reviewmentioning
confidence: 99%